Event-management: Review and Systematization of Approaches of the Organization of Events - Sergey Gennadievich Ermakov; Julia Alekseevna Makarenko; Nikolay Evgenievich Sokolov (Управленческое консультирование)
Event management is one of the most effective method of the promotion for companies de veloping innovative products and services and working in areas of the management consulting and system integration. Approaches of the organization of large mass actions which creating information occasions for participants and forming their publicity are analyzed in the article. Key features of the event management for innovative types of business and management consulting are considered. The recommendations describing the model and structure of the life cycle of mass events are also developed in the article.